Our Spirits Do Not Speak English: reflections on the western schooling process and the attempts to assimilate and acculturation of indigenous peoples (Research, Society and Development, 2022)
This article aims to understand the civilizing process in the West, the emergence of western schooling and the attempts at assimilation and acculturation committed to indigenous peoples based on the analysis of the documentary Our spirits do not speak English. In this historical context of the western schooling of indigenous peoples, we will tread obscure paths and discover the hidden face of school because it is a castrating and domesticating educational practice, imposed by the supposed superior western culture that tries to erase the memories, cultures and identities of indigenous peoples by forcing a practice of assimilation and acculturation of their ways of life. Methodologically, it is a theoretical study with a historiographical approach, making use of documentary research, having as data collection instruments, the technique of transcription and minutes of the documentary and the technique of capturing images. It is concluded that indigenous peoples were never passive in this process, on the contrary, there were resistance groups organized by the elders of the tribes in defense of the right to maintain their ethnic and cultural origins due to the fact that their spirits did not speak English, but multiple languages. indigenous.